Nigeria zero hunger/IITA policy brief No. 4: Nigeria zero hunger strategic review - nutritional status of children under the age of 5 in Sokoto state, Nigeria - Okike, Iheanacho; Ayoola, G.B.; Ogundapo, A.T.; Ojide, M.; Abdoulaye, Tahirou; Dashiell, Kenton E.; Manyong, Victor (Herald Scholarly Open Access, 2021)
The United Nations’ “2030 Agenda for Sustainable Development” (also known as Sustainable Development Goals - SDGs) has 17 goals [1], to which the Federal Republic of Nigeria committed to achieving.